Research of academic giftedness in foreign studies: socio-psychological aspect - Meshkova N.V. (Современная зарубежная психология, 2015)
The article provides an overview of foreign publications on the issue of giftedness. Particular attention is paid to the socio-psychological aspect of education of gifted schoolchildren with the help of programs for the accelerated and in special classes. The article reviews the results of studies examining implicit views of ordinary students and school teachers on the gifted as well as a point of view of classmates, parents, teachers and the gifted themselves on gifted students. It describes the strategies for social interaction in academically gifted students who become the victims of bulling. The article analyses the data, obtained in a series of studies, which demonstrate the negative and positive effects of the classroom and family contexts on the academic and social competences of gifted students. The features of academic and social self-concept; relationships with classmates; interactions with adults (parents and teachers) are regarded in the article as contexts supporting the students’ academic achievement potential, which may remain in some cases not realizedal.